The spatial characteristics of traditional Terengganu architecture towards enhancement of coastal resort tourism identity in Terengganu / Izzati Zainal Abidin ... [et al.] - Zainal Abidin, Izzati; Ismail, Sumarni; Ismail, Nor'atiah; May Ling, Siow; Mohd Hamdan, Nur Aina Abidah (Universiti Teknologi MARA, Perak, 2024)
Terengganu's identity can adapt and consolidate to form its own character because of its commercial and cultural ties with neighbouring Siam, Cambodia, and Indonesia. Terengganu's traditional architecture has been shaped by all these influences and is considered the cradle of Malay civilization. The ability to adapt has strengthened the country's uniqueness and identity. However, indigenous cultures are believed to be losing their identity as globalisation continues. The loss of identity of Terengganu's traditional architecture has a strong impact on the community, which views Malay culture in the form of resort architecture as indestructible and immediately rejects it as a cheap imitation that does not reflect the authenticity of Terengganu's regional identity. This study aimed to identify the spatial characteristics of traditional Terengganu architecture. Some of the methods used to investigate the spatial characteristics of traditional Terengganu architecture include document review, personal interviews with the resort owner, and field surveys and observations. To achieve this objective, the aim of this study was to investigate the architectural features of traditional Terengganu architecture, particularly in terms of spatial features as part of the traditional Terengganu architectural identity on the east coast of Peninsular Malaysia. A field mapping for the case study analysis was conducted at Terrapuri Heritage Village in Setiu, Terengganu, and a total of three (3) buildings from the case study site were considered. The results of the study show that some adjustments were made to the layout of the rooms according to the function of the resort. These include the adaptation/reuse of the room layout, such as converting the kitchen area (dapur) into a bathing area, reconstructing the old structure, and adopting the architectural form with modern materials and construction. The results of this study illustrate a valuable traditional Terengganu architecture in terms of spatial features that preserve at least part of the traditional Malay socio-cultural values and regional identity of Terengganu while meeting the pressures of twenty-first century design constraints.